The educational potential of collaborative writing mediated by digital technology in times of pandemic: a scoping review - Liverano Giuseppe (Research on Education and Media)
Today’s schools must respond to the evolving needs of students by adopting new pedagogical models and didactic devices. Information and communication technologies can be useful resources to focus on the learning of each individual student as a dynamic and relational process. Collaborative writing apps facilitate democratic and shared construction of knowledge through ICT (Van Leeuwen, Janssen, 2019). This approach fosters the transformation of knowledge through a trialogical approach to learning (Cesareni et al., 2018). This article analyzes the responses of a collaborative writing experience with apps in a school. The aim of this contribution is to highlight the most effective technology-mediated collaborative writing interventions that have been implemented during the Covid-19 pandemic. The focus is on their educational potential in terms of both cognitive and non-cognitive skills.